Komunikasi Lingkungan Pengelolaan Sampah Program Kangpisman di Kota Bandung - Nugraha, Fajar (Departemen Komunikasi dan Penyiaran Islam, 2024)
Bandung City faces a major problem in waste management, which continues to increase, reaching 1,609.76 m³/day by 2023. The ‘collect-transport-dispose’ paradigm of waste management still dominates, causing accumulation in landfills located far from the city centre. As a solution, the Bandung City Government initiated the Kangpisman (Reduce, Separate, Utilise waste) programme that involves collaboration between the government, the community, and the private sector. This research aims to describe how environmental communication on waste management in the kangpisman programme occurs among stakeholders in the city of Bandung. This research uses a qualitative approach with a literature study to analyse environmental communication in the Kangpisman program. The results showed that the Kangpisman programme became a form of symbolic action in environmental communication through the main message of reducing, separating and utilising waste as waste management. The communication channels used to deliver the Kangpisman programme messages are very diverse ranging from social media, local television and radio to face-to-face education to increase public awareness.